A Review of Maslahah on Salah Aku Apa Program by the Disdukcapil of South Solok Regency, Indonesia - Shafra, Shafra; jayusman, jayusman; Putra, Andi Eka; Bunyamin, Mahmudin; Dilla, Dilla (Universitas Islam Negeri Raden Intan Lampung, 2024)
This study examined the innovative program Salah Aku Apa, initiated by the Disdukcapil (Population and Civil Registration Office) of South Solok Regency, West Sumatra. It was analyzed through the theory of maslahah (public benefit). The research was motivated by the achievements of the Disdukcapil of South Solok Regency, which received an award as a high-category (green) Public Service Organizer unit from the Ombudsman of the Republic of Indonesia. This study aims to analyze the maslahah perspective on the Salah Aku Apa program from Disdukcapil of South Solok Regency. The research method employed was field research with a descriptive-analytical nature. The primary data was obtained through interviews with several relevant parties, complemented by secondary data. The data collecting techniques were interviews, documentation, and observation, followed by inductive analysis to conclude. The program was proven to provide convenience to the community. It was considered friendly to mothers and children, as it facilitated the process for mothers who had recently given birth to obtain civil registration documents for their newborns. The study concluded that the